PENGARUH KOMITMEN ORGANISASI DAN KOMPENSASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR DENGAN LOYALITAS GURU SEBAGAI VARIABEL INTERVENING (STUDI PADA TENAGA GURU DI AMAL USAHA MAJELIS DIKDASMEN MUHAMMADIYAH KOTA PEMATANG SIANTAR) - Ritonga, Juleha; Khair, Hazmanan; Rambe, Muis Fauzi (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, Universitas Muslim Nusantara Al-Washliyah, 2024)
This study aims to test and analyze the effect of organizational commitment, compensation, on organizational citizenship behavior mediated by teacher loyalty in the Amal Usaha Majelis Dikdasmen Muhammadiyah Pematangsiantar. The data used in this study were obtained directly from respondents totaling 54 permanent teachers of Perguruan Muhammadiyah Pematangsiantar which were processed with the help of the SmartPLS program. The results showed that organizational commitment, teacher loyalty, individually had a significant effect on organizational citizenship behavior. While compensation with a negative direction has an insignificant effect on organizational citizenship behavior. Organizational commitment variables, compensation, individually have a significant effect on teacher loyalty. Teacher loyalty significantly mediates the effect of organizational commitment on organizational citizenship behavior. Loyalty significantly mediates the effect of compensation on organizational citizenship behavior.